Schaum's outline series theroy and problems of electromagnetics - Edminister, Joseph A.; Edminister, Joseph A. (New York, McGraw hill, Inc., 1993)
Like the popular previous edition, this valuable study guide keeps the mathematics as simple as possible and includes numerous concrete examples of concepts and principles, plus graphs and sketches to illuminate important points. New in this edition are chapters on transmission lines, waveguides and antennas, making this powerful study tool even more useful for both students and practitioners using electromagnetic field theory. Table of Content: Vector Analysis Coulomb Forces and Electric Field Intensity Electric Flux and Gauss' Law Divergence and the Divergence Theorem The Electrostatic Field: Work, Energy, and Potential Current, Current Density, and Conductors Capacitance and Dielectric Materials Laplace's Equation Ampere's Law and the Magnetic Field Forces and Torques in Magnetic Fields Inductance and Magnetic Circuits Displacement Current and Induced E
Appendix 315-316p.; Index 317-322p.
Keywords: Electromegnatics; Transmission lines; Vector analysis; Physics